The CO2CRC Otway shallow CO2 controlled release experiment: Fault characterization and geophysical monitoring design. (July 2022) - Feitz, A.; Radke, B.; Ricard, L.; Glubokovskikh, S.; Kalinowski, A.; Wang, L.; Tenthorey, E.; Schaa, R.; Tertyshnikov, K.; Schacht, U.; Chan, K.; Jordana, S.; et al.
Highlights: Large multidisciplinary study sheds light on the fault and host rock properties that facilitate vertical CO2 migration at a strike-slip fault Detailed geological model of a strike-slip fault in carbonate rock Modelling suggests that migration of CO2 up a fault can be tracked using reverse 4D vertical seismic profiling, offering a potentially useful contingency monitoring technique. Abstract: CO2CRC has made a significant investment into establishing the feasibility of conducting a CO2 injection experiment into a shallow fault at the CO2CRC Otway International Test Centre. Two appraisal wells drilled and cored through Brumbys Fault indicate the fault extends to the base of the upper 2 m thick Hesse Clay layer, which forms a seal to the underlying Port Campbell Limestone aquifer. The fault does not have a defined core; rather, it is expressed by an approximately 6-10 m wide cataclastic zone. Permeability within the Port Campbell Limestone is variable, ranging from tens to thousands of millidarcies (10 −14 to 10 −12 m 2 ). The rock strength is low and it is recommended to conduct the experiment at approximately 80 m depth rather than the 40 m originally proposed. This provides more confining pressure and will ensure that the injection pressure does not exceed the fracture pressure. A deeper injection also provides better spatial and timing conditions for geophysical monitoring and tracking of the CO2 plume. Simulations indicate that a 10 t CO2 injection experiment would be sufficient to monitor CO2 migration using geophysical techniques and the planned deployment of reverse 4D vertical seismic profiling would be able to track this small quantity of CO2 up a fault. In addition to providing an opportunity to demonstrate semi-continuous, near real-time monitoring of CO2 migration up a fault, the planned CO2 injection experiment presents a unique opportunity to obtain field measurements on vertical fault permeability at a shallow strike-slip fault.